Continuous Audit: Implementasi dan Pengendalian Berbasis Teknologi Informasi dalam Menjalankan Fungsi Audit yang lebih Efektif dan Efisien - Hiererra, Siti Elda; Sarayar, Mario Octaviano Ignatius (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Information Technology (IT) continues to transform how organizations function, communicate and do business with customers, partners and agents. Directors, audit committee, management and stakeholders sincerely hope their auditors more adept at using technology both in the field of audit (Audit Leveraging Technology) to develop a thorough understanding of how they control the company's processes and internal controls. The research methodology to be used is quantitative observation methodology, by collecting data from various data sources such as journals and literature on Continuous Auditing, both best practice (Practical Approach) as well as theoretical and raw concept of Continuous Auditing (Teorical Approach). Impact on the internal audit process and methodology by using Continuous Audit will be very revolutionary and a major impact on the development of the company's business and also the audit function which is run by the company.